'The teacher almost made me cry' Narrative analysis of teachers' reactive classroom management strategies as reported by students diagnosed with ADHD. (April 2016) - Honkasilta, Juho; Vehkakoski, Tanja; Vehmas, Simo
Abstract: This interview study addresses the gap in earlier research by focussing on the narratives of 13 ADHD-diagnosed Finnish students regarding teacher reactive classroom management strategies. The data are analysed through narrative analysis. Five different narrative types are identified, in which teacher behaviour is evaluated as (1) disproportionate, (2) traumatising, (3) neglectful, (4) unfair and (5) understanding. The dominant storyline – common to the first four types – constructed the narrator's transgression as contingent upon and a justified reaction to teacher conduct. The vicious cycle of coercive classroom management strategies and the culture of blame between students and teachers are discussed. Highlights: Classroom management is studied from the viewpoint of ADHD-diagnosed students. A narrative approach is applied to analyse student interviews. Students produced negative evaluations of teachers' classroom management strategies. Student resistance was constructed as a justified reaction to teacher conduct. ADHD played surprisingly minimal significance in student narratives.